Exploring the potential of plant volatiles to enhance pest management in sweet pepper plants - Riahi, Chaymaa; Urbaneja, Alberto; Gallego, Carolina; Pérez-Hedo, Mertixell (2024)
Herbivore-induced plant volatiles (HIPVs) mediate plant-to-plant communication and are received by plants as warning cues to avoid herbivore attacks. Hence, exposure to HIPVs induces a defensive response and enhances plant resistance against phytophagous arthropods and diseases. Furthermore, HIPVs attract beneficial organisms, including predators and parasitoids, providing additional pest control benefits. This work highlights the role of HIPVs as a sustainable and biorational approach to managing sweet pepper pests. In particular, the potential of one of these HIPVs, the green leaf volatile (Z)-3-hexenyl propanoate, to control three sweet pepper key pests, Spodoptera exigua, Frankliniella occidentalis, and Trialeurodes vaporariorum, was assessed. In greenhouse experiments, the infestation levels of the three pests were significantly reduced in sweet pepper plants exposed to the volatile compared to nonexposed plants. These findings highlight the promising role of HIPVs as sustainable and biorational tools for sweet pepper pest management. To fully exploit the benefits of this approach, future research should focus on integrating HIVS effectively with existing pest management strategies for sweet pepper crops.